ENHANCING PROCEDURAL TEXT LEARNING: A STUDY ON ELECTRONIC TEACHING MATERIALS FOR MIDDLE SCHOOL STUDENTS - Masitah Intan Sari Hasibuan; Wisman Hadi; Muharrina Harahap (Curricula: Journal of Teaching and Learning, 2024)
This research investigates the feasibility and effectiveness of innovative electronic teaching materials designed for teaching procedural texts to Phase D learners at SMP Negeri 1 Percut Sei Tuan. Utilizing a Research and Development (R&D) approach, this study incorporates the ADDIE model for systematic development and evaluation. The materials developed were assessed by material and media experts, with a sample group comprising 26 seventh-grade students from class VII-1. The evaluation by material experts resulted in a high feasibility score of 93%, while mediaexperts provided an approval rating of 86%, indicating strong validation from both perspectives. The educational effectiveness of these materials was further tested through a practical classroom application, where students' performance was measured using pretest and posttest scores. Initially, students scored an average of 70 in the pretest. After the implementation of the electronic materials, the average posttest score rose significantly to 87. These results suggest that the electronic teaching materials for procedural texts are not only highly feasible according to expert validators but also effectively enhance learning outcomes among seventh graders at SMP Negeri 1 Percut Sei Tuan. Consequently, these materials are recommended for use as supplementary teaching resources in the Indonesian language curriculum, particularly beneficial for Phase D learners. The study confirms the potential of integrating innovative electronic materials into traditional educational settings to improve understanding and engagement among students.